2009
DOI: 10.1111/j.1467-839x.2009.01278.x
|View full text |Cite
|
Sign up to set email alerts
|

Is self‐esteem a universal need? Evidence from The People's Republic of China

Abstract: In a provocative article, Heine et al. concluded that self‐esteem needs are less important in collectivistic, East Asian countries than in individualistic, Western ones. Their conclusion was based, in part, on evidence that: (i) self‐esteem scores are less positively biased in Japan than in Western countries; and that (ii) low self‐esteem is less predictive of psychological distress in Japan than in Western countries. The present research examined whether these cultural differences occur in another collectivis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
46
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 68 publications
(53 citation statements)
references
References 42 publications
6
46
0
Order By: Relevance
“…Examining the cross-cultural validity of the present findings is particularly important, because there is an ongoing debate about whether members of collectivistic cultures show the same need for self-esteem and the same level of narcissism and self-enhancement bias as do members of individualistic cultures (Cai, Wu, & Brown, 2009;Heine, 2005;Heine & Hamamura, 2007;Heine, Lehman, Markus, & Kitayama, 1999;Sedikides, Gaertner, & Toguchi, 2003;Sedikides, Gaertner, & Vevea, 2005). Therefore, future research should test whether genuine self-esteem and pure narcissism show different relations with depression in collectivistic versus individualistic cultural contexts.…”
Section: Limitations and Future Directionsmentioning
confidence: 80%
“…Examining the cross-cultural validity of the present findings is particularly important, because there is an ongoing debate about whether members of collectivistic cultures show the same need for self-esteem and the same level of narcissism and self-enhancement bias as do members of individualistic cultures (Cai, Wu, & Brown, 2009;Heine, 2005;Heine & Hamamura, 2007;Heine, Lehman, Markus, & Kitayama, 1999;Sedikides, Gaertner, & Toguchi, 2003;Sedikides, Gaertner, & Vevea, 2005). Therefore, future research should test whether genuine self-esteem and pure narcissism show different relations with depression in collectivistic versus individualistic cultural contexts.…”
Section: Limitations and Future Directionsmentioning
confidence: 80%
“…As shown by Lee et al (2010), temporarily activating an individual or collective mindset (by giving instructions to bilingual participants in either English or Chinese language) influences self-enhancement (reported in a relatively public group setting). Our findings suggest that such activation would influence other selfenhancement strategies in a complementary manner; that is, whereas a collective mindset would temporarily reduce positivity embracement, it would increase favorable construals and (Brown, 2010;Cai et al, 2009;Gaertner et al, 2008), it would be informative to examine systematically the consequences of promotion-focused versus prevention-focused selfenhancement/protection strategies for well-being across cultures.…”
Section: Self-enhancement and Self-protection In China 16mentioning
confidence: 99%
“…Given the evidence for consistent correlates of betterthan-average self-views and self-serving attributions across cultures Cai et al, 2009;Gaertner et al, 2008;Kobayashi & Brown, 2003), we hypothesized that the use of different strategies would be subject to the same individual differences in China as in Western samples (cf. Hepper et al, 2010;Hypothesis 3).…”
Section: The Present Investigationmentioning
confidence: 99%
See 1 more Smart Citation
“…However, given that the present research is the first systematic examination of the effects of mortality salience and self-esteem on psychological adjustment, it is important to demonstrate that the observed pattern of findings is obtained in a culturally distinct sample. In addition, although there is now a sizable literature in support of the assertion that self-esteem is a universal need (Brown, in press;Cai, Brown, Deng, & Oakes, 2007;Cai, Wu, & Brown, 2009; Sedikides, Gaertner, & Toguchi, 2003; Sedikides, Gaertner, & Vevea, 2005Yamaguchi et al, 2007), replicating the effects observed in the first four studies in a non-Western sample would provide convergent evidence for the universality of the self-esteem motive by demonstrating that self-esteem buffers the effects of death-related cognition on psychological adjustment similarly in distinct cultural samples. Therefore, in Study 5, we examined the effects of mortality salience and self-esteem on meaning using a sample of Chinese college students.…”
Section: Studymentioning
confidence: 99%